Differential effects of dietary and physical activity interventions on adiposity of children with obesity - Anekchoke Tangtongsoong; Chonnikant Visuthranukul; Yuda Chongpison; Sirinuch Chomtho (Clinical and Experimental Pediatrics)
Background Managing obesity in children remains challenging. In addition to body mass index (BMI), incorporating body composition into evaluations of postobesity interventions would help assess changes in adiposity. Purpose This study aimed to identify the relationship between dietary intake, physical activity, and changes in BMI z scores and adiposity among children with obesity. Methods Children aged 7–15 years with obesity received monthly dietary and physical activity instructions for 6 months. Three-day dietary records and physical activity questionnaires were collected at 0, 3, and 6 months. Body composition was measured using bioelectrical impedance analysis. These relationships were analyzed using uni- and multivariate linear regression analyses. Results A total of 155 children with obesity completed the 6-month study. A higher total protein intake per ideal weight for height was significantly correlated with a decrease in BMI z score and trunk fat mass index (trunk fat mass [FM] in kg/height in m2). Mean dietary fiber intake was negatively correlated with BMI z score, FM, FM index (FMI, FM in kg/height in m2), and visceral fat area (VFA) at 6 months. Each 1 g/kg/day increase in protein intake and additional 1 g/day of dietary fiber intake led to a 0.191 kg/m2 (95% confidence interval [CI], -0.309 to -0.072) and 0.028 kg/m2 (-0.05 to -0.005) reduction in BMI z score. Each 1 g/day increase in protein intake led to a reduction of 0.009 kg/m² in trunk FMI (-0.016 to -0.002) and 0.21 cm² in VFA (-0.418 to -0.002). The outcomes observed at 6 months were consistent with the overall 6-month findings, reinforcing the efficacy of the intervention. Conclusion Our study showed beneficial effects of high dietary protein and fiber intakes on BMI z scores and adiposity of children with obesity. Fine-tuning dietary interventions that emphasize appropriate protein and fiber intakes may be more practical for managing childhood obesity.